Modified Gegen Qinlian Decoction Ameliorates DSS-Induced Ulcerative Colitis in Mice by Inhibiting Ferroptosis via Nrf2/GPX4 Pathway - Jinke Huang; Jiaqi Zhang; Zhihong Liu; Jing Ma; Fengyun Wang; Xudong Tang (Journal of Food Quality)
Objective. Ferroptosis, a form of programmed cell death, is considered a novel target for the treatment of ulcerative colitis (UC). The aim of this study was to explore whether modified Gegen Qinlian decoction (MGQD) ameliorates UC in mice via mediating ferroptosis. Methods. Mice with dextran sulfate sodium- (DSS-) induced colitis were administered with MGQD for seven days. Subsequently, iron, malondialdehyde (MDA), glutathione (GSH), and reactive oxygen species (ROS) were measured. ELISA and immunohistochemistry were used to evaluate the levels of proinflammatory cytokines and tight junction proteins, respectively. Transmission electron microscopy was used to reveal mitochondrial morphology. Western blot and qRT-PCR analyses were used to assess the expression levels of the proteins of Nrf2/GPX4 pathway. The docking affinity of MGQD and Nrf2 was assessed using AutoDock Vina 1.1.2. Results. Ferroptosis was identified in mice with UC, as demonstrated by mitochondrial disruption, MDA and ROS production, iron overload, decrease in GSH level, and abnormal expression of core marker proteins of ferroptosis. After MGQD treatment, these characteristic changes of ferroptosis were significantly reversed, along with concomitant activation of the Nrf2/GPX4 pathway. Furthermore, molecular docking analysis revealed that MGQD had a high affinity for Nrf2. Conclusion. MGQD may ameliorate UC by inhibiting ferroptosis via the activation of Nrf2/GPX4 pathway. This study provided new insights into the application of MGQD complementary therapy for UC.